2018
DOI: 10.1038/s41559-018-0642-z
|View full text |Cite
|
Sign up to set email alerts
|

The evolutionary landscape of colorectal tumorigenesis

Abstract: The evolutionary events that cause colorectal adenomas (benign) to progress to carcinomas (malignant) remain largely undetermined. Using multi-region genome and exome sequencing of 24 benign and malignant colorectal tumours, we investigate the evolutionary fitness landscape occupied by these neoplasms. Unlike carcinomas, advanced adenomas frequently harbour sub-clonal driver mutations-considered to be functionally important in the carcinogenic process-that have not swept to fixation, and have relatively high g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
142
3
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 107 publications
(173 citation statements)
references
References 39 publications
23
142
3
2
Order By: Relevance
“…The CADs in our adenoma cohort derive from FAP1 patients and follow the CAD-carcinoma sequence, where loss of the tumor suppressor gene APC appears as the first most frequent genetic event at the origin of the adenoma [1,8,38]. Accordingly, we found that CADs were aberrantly activated for the Wnt/β-catenin signaling, this being supported by the numerous upregulated β-catenin targets in these adenomas (DEFA6, REG3A, REG1A, EPHB2, EPHB3, see supplementary material, Table S3) and also by the overexpression of the intestinal stem cell marker OLFM4 (supplementary material, Table S3).…”
Section: Discussionmentioning
confidence: 99%
“…The CADs in our adenoma cohort derive from FAP1 patients and follow the CAD-carcinoma sequence, where loss of the tumor suppressor gene APC appears as the first most frequent genetic event at the origin of the adenoma [1,8,38]. Accordingly, we found that CADs were aberrantly activated for the Wnt/β-catenin signaling, this being supported by the numerous upregulated β-catenin targets in these adenomas (DEFA6, REG3A, REG1A, EPHB2, EPHB3, see supplementary material, Table S3) and also by the overexpression of the intestinal stem cell marker OLFM4 (supplementary material, Table S3).…”
Section: Discussionmentioning
confidence: 99%
“…We now proceed to in vivo per--cell mutation rates within individual human tumours. A unique sample set 21 (1) above. Simulations show that inferences are possible with as few as 6 tumour samples (SI Figure 33).…”
Section: Measuring the Per--cell Mutation Rate In Individual Human Tumentioning
confidence: 99%
“…Details of the bioinformatics--analysis of the multi--region sequenced tumour samples can be found for the colon carcinomas and the adenoma in 21 , the additional three single cell whole genome sequenced colon cancers 27 the renal cell carcinomas in 29 and the lung squamous and adenocarcinoma in 28 . Details on the methodology and sequencing of single stem cells in healthy haematopoiesis can be found in 20 .…”
Section: Genomic Analysis Of Cancer Samplesmentioning
confidence: 99%
See 2 more Smart Citations